(untitled) (Linguostylistic Studies, 2016)
This research is an attempt to describe the linguistic and stylistic peculiarities of such an old Ukrainian literary language functional variety, as private epistolary. Chronology of the analyzed material (XVIII-th century) covers the time, when the basic features of the literary language of the Ukrainian nation had been already firmly established. Colloquial version of Ukrainian national language appeared to be an important basis for the formation of the literary language. The author emphasizes that it is a fundamental factor, which stimulates the study of the Ukrainian language annals, approximated to the spoken elements. «Private correspondence of the eighteenth century» is an important historical source, the study of which allows to examine objectively the ways of formation and development of the Ukrainian language standards, and explore the relationship of the bookish and colloquial elements. Epistolary of XVIII-th century is analyzed in the article as a conglomerate of language elements, different by their origin and stylistic features, among which a special place belongs to the nominations of the addressee, namely the obligatory clichéd components used in the specified style of language material. The analysis allows to conclude that an addressee could be referred to in different ways, from single words to extended word combinations. Key words: diachronic aspect, epistolary style, nomination, addressee, thematic groups of vocabulary, colloquial words, bookish words, primordial lexical items, borrowings. References